Fostoria dhimbangunmal, gen. et sp. nov., a new iguanodontian (Dinosauria, Ornithopoda) from the mid-Cretaceous of Lightning Ridge, New South Wales, Australia. Issue 1 (2nd January 2019) - Bell, Phil R.; Brougham, Tom; Herne, Matthew C.; Frauenfelder, Timothy; Smith, Elizabeth T.
ABSTRACT: Globally, non-hadrosauroid iguanodontians ('basal iguanodontians') reached their acme in terms of diversity during the Early Cretaceous. However, Gondwanan representatives of this clade are rare and are represented in Australia only by the enigmatic Muttaburrasaurus langdoni (upper Albian; Mackunda Formation) . Here, we describe a new iguanodontian, Fostoria dhimbangunmal, gen. et sp. nov ., from the Cenomanian Griman Creek Formation at Lightning Ridge, New South Wales, Australia. The holotype and referred specimens, preserved entirely in opal, pertain to at least four individuals from a monodominant bone bed excavated from an underground opal mine. This deposit constitutes the first ornithopod-dominated bone bed from Australia. Elements from most parts of the body are represented, including the first partial skull of a dinosaur recovered from New South Wales. The new taxon is identified by a number of autapomorphies that include, but are not restricted to, a stepped lateral margin of the frontal in dorsal view and a stout protuberance on the anterolateral corner of the frontal. Phylogenetic analysis based on a recently published data set recovers Fostoria as the sister taxon to a clade of Gondwanan iguanodontians that includes Anabisetia saldiviai, Talenkauen santacrucensis, and Muttaburrasaurus langdoni . The new taxon and M. langdoni represent the sole iguanodontians known from the eastern margin of the epeiric Eromanga Sea, whereas the group is conspicuously absent from the contemporaneous ornithopod-dominated ecosystems of the Australian-Antarctic rift valley in Victoria.